f(x) = x/(x + 1)
To find the inverse, first, let y = f(x). Then
y = x/(x + 1)
Like you already know, swap the x and y terms.
x = y/(y + 1)
And now, solve for y. Multiply both sides by (y + 1),
x(y + 1) = y
Now, expand the left hand side.
xy + x = y
Bring everything with a y to the left hand side, and everything else to the right hand side.
xy - y = -x
Now, factor y out, on the left hand side.
y(x - 1) = -x
Divide both sides by (x - 1), to get
y = -x / (x - 1)
All that's missing is your concluding statement. Remember that you wanted to solve for f^(-1)(x), so that's what you say.
Therefore,
f^(-1)(x) = -x / (x - 1)
2007-01-18 12:51:56
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Many have answered, so I won't repeat what has been said. However, it is a good idea to check your solution if you are not comfortable with the process.
To check, select a number for x. If you chose x = 1, f(x) = 1/ 1+1 = 1/2. Therefore, in the inverse function, if I substiture the answer 1/2 in for x, I should get 1 as my y, or f^-1(x)
2007-01-18 13:04:13
·
answer #2
·
answered by Pythagoras 7
·
0⤊
0⤋
Step 1) put y in place of f(x)
Step 2) Switch the x's and y's (put an x where the y was, and put y's where the x's are
Step 3) Solve for y
Step 4) you have the inverse function
2007-01-18 12:49:42
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
y=x for a inverse relation deliver you modify y<=> x ie reflect the function interior the line y=x outline the relation deliver f (g) = g(f) for strict inverse function you want to restriction the domains and levels of both relations contributors f & g such that f & g are purposes you may now outline the invertible function. seem up the definition of a function and also you may want to make certain that is somewhat trivial. degenerate case the x axis (function) invert, the y axis (no longer and by no ability a function) this can be generalized
2016-10-15 10:30:27
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
I remember this one. This problem was invented by Archimedes and is called the "Are you a tricky little bugger" problem. The trick (after three pages of desperate scribbling) is this:
x/(x+1) = y
=> (xy + y)/x = 1
=> y + (y/x) = 1
=> y/x = 1 - y
=> y = x(1-y)
=> y/(1-y) = x
And switch x and y as normal. I see someone solved this an hour ago, but at least I have my dignity.
2007-01-18 13:45:51
·
answer #5
·
answered by Steven X 1
·
0⤊
0⤋
ok so you rewrite as f(x) = y = x/(x+1)
Now to get the inverse you switch y and x. You now get:
g(x) = inverse of f(x)
x = y/(y+1)
y = x*(y+1) = xy + x
y - xy = x
y*(1-x) = x
g(x) = y = x/(1-x)
2007-01-18 12:53:04
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
let y=x/(x+1);
y(x+1)=x;
yx+y=x;
y=x-yx;
x(1-y)=y;
rearranging the equation for x in such a way--
x=y/(1-y);
and now replace 'x' with 'y'
i.e y=x/(1-y)...its Ur answer
2007-01-18 12:53:09
·
answer #7
·
answered by Andrew goel 2
·
0⤊
1⤋
you do not replace x and y, you have to solve for x - that is isolate x instead of y on one side of the equation.
2007-01-18 12:51:12
·
answer #8
·
answered by themountainviewguy 4
·
0⤊
1⤋
1. replace f(x) with y
2. switch x and y in your equation
3. solve for y
4. rewrite y as f^-1(x)
ta-da!!!!
2007-01-18 12:49:17
·
answer #9
·
answered by Simone * 1
·
0⤊
1⤋
f(x)= x/(x+1)
x=y/(y+1)...
Don't remember the rest. Please post the answer and I might be able to finish
2007-01-18 12:51:00
·
answer #10
·
answered by Christiansoccerchica 2
·
0⤊
1⤋